2020
DOI: 10.1007/s00268-020-05444-y
|View full text |Cite
|
Sign up to set email alerts
|

Diltiazem Prophylaxis for the Prevention of Atrial Fibrillation in Patients Undergoing Thoracoabdominal Esophagectomy: A Retrospective Cohort Study

Abstract: Background Atrial fibrillation (AF) represents the most frequent arrhythmic disorder after thoracoabdominal esophageal resection and is associated with a significant increase in perioperative morbidity and mortality.Methods In this retrospective cohort study, 167 patients who underwent thoracoabdominal esophagectomy at a large university hospital were assessed. We compared patients who received a 14-day postoperative course of diltiazem with a control group of patients who did not undergo diltiazem prophylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Prophylactic amiodarone could lower incidence of postoperative AF in patients undergoing pulmonary resection [ 3 ], as well as in patients undergoing esophagectomy [ 4 ]. Similar findings have been reported with other pharmacological conversion agents, including diltiazem [ 5 ] and metoprolol [ 6 ]. The objective of the current study was to examine whether intraoperative use of pharmacological conversion in new AF patients with general thoracic operations could help to restore sinus rhythm.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Prophylactic amiodarone could lower incidence of postoperative AF in patients undergoing pulmonary resection [ 3 ], as well as in patients undergoing esophagectomy [ 4 ]. Similar findings have been reported with other pharmacological conversion agents, including diltiazem [ 5 ] and metoprolol [ 6 ]. The objective of the current study was to examine whether intraoperative use of pharmacological conversion in new AF patients with general thoracic operations could help to restore sinus rhythm.…”
supporting
confidence: 89%
“…Most notably, newonset AF during surgery is primarily due to mechanical stimulation of atria and pulmonary veins and the autonomic nerves, and thus is less likely to respond to drug treatments. In contrast, prophylactic use of antiarrhythmic drugs (e.g., amiodarone, diltiazem, and metoprolol) has been shown to be effective for postoperative AF [4][5][6].…”
Section: Commentmentioning
confidence: 99%
“…Hochreiter et al, in 2020, found that diltiazem did not reduce the incidence of POAF following thoracoabdominal esophagectomy. At the same time, its use was associated with several side effects [67]. Lederer et al, in a very recent study, showed that diltiazem prophylaxis was not useful in reducing POAF incidence after thoracoscopic lobectomy [68].…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Unfortunately, a multitude of shortcomings plague this topic in that the studies focused only on very specific cardiac surgeries such as CABG, and the arrhythmias studied were limited to specific arrhythmias only, namely AFib [77]. Another condition that holds potential is the cohort of patients given prophylactic amiodarone combined with a non-antiarrhythmic.…”
Section: Future Applications and Limitationsmentioning
confidence: 99%